REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis - Bayram, Yavuz; White, Janson J.; Elcioglu, Nursel; Cho, Megan T.; Zadeh, Neda; Gedikbasi, Asuman; Lupski, James R. (Cell Press, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exontruncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Transcription Factor Rest; Restrictive Silencer Factor; Gene-Expression; Neuroendocrine Differentiation; Signaling Pathway; Repressor; Cancer; Fibroblasts; Protein; Tumor